"We serve too!": Everyday militarism of children of US service members. (August 2020) - Frain, Sylvia C; Frain, Betty
There are 2 million United States military–attached children worldwide; however, the US government does not track the data of those who commit suicide. Military children's daily lives are affected by the everyday and slow violence of constantly preparing for war. This article conducts a critical content analysis of family resiliency resources and children's books to highlight the ongoing need for structural change. We conclude with recommendations on how to best address the specific needs of military-attached children.